DCAF4L2 promotes colorectal cancer invasion and metastasis via mediating degradation of NFκb negative regulator PPM1B - Wang, Haiyu (Am J Transl Res, 2016)
DCAF4L2 is a member of WD-repeat proteins, which commonly serve as mediators of protein-protein interplay. In this study, we reported that elevated DCAF4L2 expression in human colorectal cancer (CRC) significantly correlated with a more advanced clinical stage as in lymphatic and distant metastasis. More importantly, elevated DCAF4L2 expression is an independent prognosis factor for survival. Genetic perturbations demonstrated that DCAF4L2 overexpression in CRC cells promoted cell migration and invasion, whereas knockdown of which had opposing effects. Moreover we discovered that DCAF4L2 overexpression could promote epithelial-mesenchymal-transition (EMT) through activating NFκB signal pathway. Mass spectrometry analysis showed that DCAF4L2 could form an E3 ligase complex with Cul4A and DDB1 thus mediated degradation of PPM1B, which has been reported to negatively regulate NFκB signaling. We identified PPM1B as a substrate of Cul4A-DDB1-DCAF4L2 E3 ligase complex, as knockdown of PPM1B abrogated shDCAF4L2 mediated inhibition of cell invasion in CRC cells. For further verification, DCAF4L2 expression inversely correlated with PPM1B expression in a cohort of 87 CRC patients. These findings may provide insight into the understanding of DCAF4L2 as a novel critical factor and a candidate target for CRC treatment.